Promoting effect of interfacial hole accumulation on photoelectrochemical water oxidation in BiVO4 and Mo-doped BiVO4 - Xiaofeng Wu; Freddy E. Oropeza; Shixin Chang; Marcus Einert; Qingyang Wu; Clément Maheu; Julia Gallenberger; Chuanmu Tian; Kangle Lv; Jan P. Hofmann (Advanced Powder Materials, 2024)
Hole transfer at the semiconductor-electrolyte interface is a key elementary process in (photo)electrochemical (PEC) water oxidation. However, up to now, a detailed understanding of the hole transfer and the influence of surface hole density on PEC water oxidation kinetics is lacking. In this work, we propose a model for the first time in which the surface accumulated hole density in BiVO4 and Mo-doped BiVO4 samples during water oxidation can be acquired via employing illumination-dependent Mott-Schottky measurements. Based on this model, some results are demonstrated as below: (1) Although the surface hole density increases when increasing light intensity and applied potential, the hole transfer rate remains linearly proportional to surface hole density on a log-log scale. (2) Both water oxidation on BiVO4 and Mo-doped BiVO4 follow first-order reaction kinetics at low surface hole densities, which is in good agreement with literature. (3) We find that water oxidation active sites in both BiVO4 and Mo-doped BiVO4 are very likely to be Bi5+, which are produced by photoexcited or/and electro-induced surface holes, rather than VOx species or Mo6+ due to their insufficient redox potential for water oxidation. (4) Introduction of Mo doping brings about higher OER activity of BiVO4, as it suppresses the recombination rate of surface holes and increases formation of Bi5+. This surface hole model offers a general approach for the quantification of surface hole density in the field of semiconductor photoelectrocatalysis.